ANALYSIS OF SURGICAL PATHOLOGY IN THE HORSE CLUB “HORSE RIDING IN POLTAVA” - Kulynych, S. M.; Omelchenko, G. O.; Avramenko, N. O.; Zezekalo, M. A.; Mostovy, S. O. (Scientific Progress & Innovations, 2020)
Non-contagious diseases, especially surgical ones, continue to cause significant harm to horses. Sick an- imals lose their ability to work for a long time, their economic value and sports performance are reduced. During the monitoring examination, the spreading, etiology and peculiarities of the course of surgical pa- thology in horses were determined. The purpose of the research was to find out the surgical pathology of horses’ orthopedic diseases in the horse club “Horse Riding in Poltava”. The research task was to analyze the frequency of occurrence and determine the causes of surgical pathology of horses’ orthopedic diseases in horses in the horse club “Horse Riding in Poltava". During the monitoring, the spreading, etiology, and pe- culiarities of horse surgical pathology of the English thoroughbred, Westphalian, Thracian, Arab, Ukrainian roadster and non-pedigree breeds, aged from 4 to 10 years, as well as ponies aged from 9 to 17 years, were determined. After that, surgical pathologies were classified according to different group,s and symptoms were determined in diseased animals. Orthopedic studies were conducted in 2018 in accordance with the methods proposed by the leading orthopedists Kyorber H. D. and Pollit K. K. The following pathologies were diagnosed by us: bruises, white line and frog putrefaction, deformities (disruption of the plantar horn, partial loss of periople, the appearance of sloping and sharp-cornered hooves) and eczematous processes on the skin. Among surgical pathologies, orthopedic diseases were the most common (45.45 %), among which inflammatory processes were most widely spread (27.27 %), the share of other forms of surgical pathology was 27.28 %. The reasons of surgical pathology were different, but they were based on the violation of zoo- hygienic conditions of keeping, the lack of timely orthopedic work (72.7 %), and traumatism (27.3 %). The development of surgical pathology was accompanied by various clinical signs, which was due to the peculi- arities of surgical pathology manifestation; in 45.4 % the onset of a chronic inflammatory reaction was reg- istered, in 27.2 % of cases the acute inflammatory reaction occurred as a result of horse injury.